2007
DOI: 10.1200/jco.2007.25.18_suppl.21053
|View full text |Cite
|
Sign up to set email alerts
|

One Step Nucleic Acid Amplification (OSNA) for intra-operative detection of lymph node metastases in breast cancer patients

Abstract: 21053 Background: Sentinel lymph node metastasis in breast cancer patients has conventionally been determined by intra- operative histopathological examination of frozen sections followed by definitive post-operative examination of permanent sections. The purpose of this study is to evaluate a more efficient method for intra-operative detection of lymph node metastasis in a clinical setting. Therefore, a new rapid method of detection of CK19 mRNA by One Step Nucleic Acid Amplification (OSNA) and Reverse Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This study has shown that across four differing hospital sites in the UK (teaching hospital, breast screening centre, cancer centre, district general hospital), the OSNA molecular assay for lymph node analysis of breast cancer patients has excellent concordance of 96·0 per cent with an intensive immunohistopathological regimen for SLN diagnosis in an intraoperative setting. It confirms the findings of four other clinical studies 8,9,13,14 , the first three of which were performed after surgery, and all of which demonstrated concordance rates greater than 93 per cent.…”
Section: Discussionsupporting
confidence: 88%
“…This study has shown that across four differing hospital sites in the UK (teaching hospital, breast screening centre, cancer centre, district general hospital), the OSNA molecular assay for lymph node analysis of breast cancer patients has excellent concordance of 96·0 per cent with an intensive immunohistopathological regimen for SLN diagnosis in an intraoperative setting. It confirms the findings of four other clinical studies 8,9,13,14 , the first three of which were performed after surgery, and all of which demonstrated concordance rates greater than 93 per cent.…”
Section: Discussionsupporting
confidence: 88%